Asia's wicked environmental problems - Stephen Howes; Paul Wyrwoll (Asian Development Bank Institute (ADBI), 2012)
The developing economies of Asia are confronted by serious environmental problems that threaten to undermine future growth, food security, and regional stability. This study considers four major environmental challenges that policymakers across developing Asia will need to address towards 2030: water management, air pollution, deforestation and land degradation, and climate change. We argue that these challenges, each unique in their own way, all exhibit the characteristics of "wicked problem". As developed in the planning literature, and now applied much more broadly, wicked problems are dynamic, complex, encompass many issues and stakeholders, and evade straightforward, lasting solutions. Detailed case studies are presented to illustrate the complexity and significance of Asia's environmental challenges, and also their nature as wicked problems. The most important implication of this finding is that there will be no easy or universal solutions to environmental problems across Asia. This is a caution against over-optimism and blueprint or formulaic solutions. It is not, however, a counsel for despair. We suggest seven general principles which may be useful across the board. These are: a focus on co-benefits; an emphasis on stakeholder participation; a commitment to scientific research; an emphasis on long-term planning; pricing reform; tackling corruption, in addition to generally bolstering institutional capacity with regard to environmental regulation; and a strengthening of regional approaches and international support.
Keywords: O44; Q58; Q56; O10; O53; Q28; Q53; 330; asia environmental problems; food security; water management; air pollution; deforestation; land degradation; climate change; wicked problems; Wasserversorgung; Luftverschmutzung; Entwaldung; Bodenbelastung; Wirtschaftswachstum; Standortfaktor; Asien